World Economy and Sustainable Political-Economic Welfare of Azerbaijan - Allahverdiyev D. I. (Randwick International of Social Science Journal, 2020)
The article examines the model of development of human well-being in the world economic system of Azerbaijan in the context of increasing political and economic relations between the states in the modern world. In this regard, the current state and prospects of cooperation in the field of economic, political relations and cooperation between the states, mutual economy, finance, organization of human welfare and human resources were studied. At the same time, political and economic proposals were made to eliminate the existing problems